1994
DOI: 10.1126/science.8290961
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D: a Downstream Effector of ARF in Granulocytes

Abstract: Activation of the phospholipase D (PLD) pathway is a widespread response when cells are activated by agonists that bind receptors on the cell surface. A 16-kD cytosolic component can reconstitute guanosine triphosphate (GTP)-mediated activation of phospholipase D in HL60 cells depleted of their cytosol by permeabilization. This factor was purified and identified as two small GTP-binding proteins, ARF1 and ARF3. Recombinant ARF1 substituted for purified ARF proteins in the reconstitution assay. These results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
394
1
2

Year Published

1995
1995
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 635 publications
(403 citation statements)
references
References 29 publications
6
394
1
2
Order By: Relevance
“…In this case, one would have to assume that this peptide, which is only 15 amino acid residues long, suffices to mediate the recruitment of these coat proteins to the TGN membrane. An alternative interpretation, which we favour, is that the stimulation of biogenesis of TGN-derived secretory vesicles by the N-myristoylated ARF1 peptide reflected the activation of phospholipase D. Phospholipase D appears to be present on Golgi membranes [29], is stimulated by ARF via ARF's myristoylated amino-terminal domain [30][31][32], and this stimulation is inhibited by brefeldin A [29]. Perhaps the Nmyristoylated ARF1 peptide was more potent in eliciting a phospholipase D activation relevant to TGN-derived secretory vesicle biogenesis than the N-myristoylated ARF4 peptide [33].…”
Section: Discussionmentioning
confidence: 88%
“…In this case, one would have to assume that this peptide, which is only 15 amino acid residues long, suffices to mediate the recruitment of these coat proteins to the TGN membrane. An alternative interpretation, which we favour, is that the stimulation of biogenesis of TGN-derived secretory vesicles by the N-myristoylated ARF1 peptide reflected the activation of phospholipase D. Phospholipase D appears to be present on Golgi membranes [29], is stimulated by ARF via ARF's myristoylated amino-terminal domain [30][31][32], and this stimulation is inhibited by brefeldin A [29]. Perhaps the Nmyristoylated ARF1 peptide was more potent in eliciting a phospholipase D activation relevant to TGN-derived secretory vesicle biogenesis than the N-myristoylated ARF4 peptide [33].…”
Section: Discussionmentioning
confidence: 88%
“…They are essential molecules for coated vesicle formation in the Golgi complex (4,5) and have also been implicated in vesicle transport between endoplasmic reticulum and Golgi (6,7) and in nuclear vesicle fusion (8). More recently, ARFs have been shown to activate phospholipase D (9,10).…”
mentioning
confidence: 99%
“…We have previously reported that bombesin-stimulated PLD activity was also regulated by guanine-nucleotides, though whether a G-protein other than Gq was involved was not determined [14]. However there is evidence that the small molecular weight G-proteins ARF [6,7] and rho [15] can regulate activity. Experiments were thus performed to investigate whether a short agonist exposure could affect the stimulation of PLD activity through G-protein activation alone.…”
Section: ~ Results and Discussionmentioning
confidence: 99%
“…It remains incompletely defined as to how an occupied cell surface receptor stimulates PLD activity, but activation has been proposed to be downstream of protein kinase C activity, tyrosine kinase activity or changes in calcium concentration, a role for the small molecular weight G-protein ARF in directly regulating PLD has also been proposed [6,7]. Bombesin-stimulated PLD activity in Swiss 3T3 cells as deter-*Corresponding author.…”
Section: Introductionmentioning
confidence: 99%